Assessing TB treatment outcomes in pregnant women living with HIV with drug-susceptible TB - N. Hernandez-Morfin; S. Cohn; Z. Waja; R.E. Chaisson; N. Martinson; N. Salazar-Austin (Public Health Action)
BACKGROUND: Limited data exist on TB treatment outcomes among pregnant women with TB. Physiological and immunological adaptations during pregnancy may affect the efficacy of TB treatment. We aimed to evaluate factors associated with unsuccessful TB treatment outcomes among pregnant women living with HIV (PWLHIV) and diagnosed with TB in the Tshepiso study. METHODS: In this secondary analysis, we used multivariable logistic regression to evaluate factors associated with unsuccessful TB treatment outcomes among PWLHIV with drug-sensitive TB disease enrolled in the Tshepiso study in Soweto, South Africa, from 2011–2014. RESULTS: This analysis includes 79 PWLHIV diagnosed with drug-sensitive TB during pregnancy; 18 (23%) had an unsuccessful treatment outcome. Factors associated with unsuccessful TB treatment include detectable HIV RNA viral load at enrollment to the study (aOR 5.1, 95% CI 1.1–25.3), presence of extrapulmonary TB (aOR 2.2, 95% CI 0.4–11.7), bacteriological (positive smear and/or culture) confirmation of TB (aOR 2.1, 95% CI 0.7–6.7), and anemia (Hb ≤ 10.5 g/dL) (aOR 1.0, 95% CI 0.3–3.1). The only factor with statistical significance was a detectable HIV RNA viral load. CONCLUSION: Detectable HIV viral load emerges as a critical factor associated with an unsuccessful TB treatment outcome in pregnant women living with HIV and diagnosed with TB.